2016
DOI: 10.1007/s13337-016-0321-0
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of the oseltamivir and Melissa officinalis L. essential oil against avian influenza A virus (H9N2)

Abstract: Lemon balm derivatives are going to acquire a novelty as natural and potent remedy for treatment of viral infections since the influenza viruses are developing resistance to the current antivirals widely. Oseltamivir, Melissa officinalis essential oil (MOEO) and their synergistic efficacy against avian influenza virus (AIV) subtype H9N2 were evaluated in vitro in MDCK cells at different time exposure by using TCID50, HA, Real Time PCR and HI assay. The results showed that MOEO could inhibit replication of AVI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 32 publications
0
45
0
1
Order By: Relevance
“…Similarly, Zeedan et al [19] reported the antiviral activity of Achillea fragrantissima against the ORF virus (a parapox virus). More recently, Pourghanbari et al [145] evaluated in vitro antiviral activity of M. officinalis (lemon balm) essential oil and oseltamivir and their synergistic effect on avian influenza virus (AIV) subtype H9N2. They found that various concentrations of lemon balm essential oil suppressed influenza virus replication.…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Zeedan et al [19] reported the antiviral activity of Achillea fragrantissima against the ORF virus (a parapox virus). More recently, Pourghanbari et al [145] evaluated in vitro antiviral activity of M. officinalis (lemon balm) essential oil and oseltamivir and their synergistic effect on avian influenza virus (AIV) subtype H9N2. They found that various concentrations of lemon balm essential oil suppressed influenza virus replication.…”
Section: Antimicrobial Effects Of Essential Oilsmentioning
confidence: 99%
“…Furthermore, sesquiterpenes are known to inhibit cytomegalovirus (CMV) early gene expression [142]. According to Pourghanbari et al [145], the essential oil of lemon balm inhibits influenza virus replication at different replication cycles by directly interacting with the virus particles.…”
Section: Mechanism Of Antimicrobial Action Of Essential Oils Againmentioning
confidence: 99%
“…Thus, a new generation of medications with completely different mechanisms of action against a broad-spectrum of influenza virus is in urgent need to better combat flu associated symptoms. A reasonably effective agent would reduce viral titer by at least 10-fold, whilst a good agent would reduce the titer 100-fold [23].…”
Section: Discussionmentioning
confidence: 99%
“…Potential synergism with conventional drugs could result in new recommendations of plant application with antiviral therapy. In revised literature, EO of Mentha suaveolens showed a synergistic effect with acyclovir against HSV-1 [69] and EO of lemon balm showed synergism with oseltamivir against avian H9N2 influenza virus [82]. In both cases, sub-optimal doses of drugs were enhanced with EOs, resulting in good antiviral activities.…”
Section: Potential Position In the Therapymentioning
confidence: 99%
“…A notable number of studies reviewed in this paper have also tried to detect the exact M-o-A of IS. This was achieved through the time-of-addition (T-o-A) study, which is comprised of assays with different procedures of addition of IS, viral suspension and cell cultures [48,[54][55][56][62][63][64]66,68,69,71,73,74,77,82,87,88,91,92,94,104,106,112]. Based on the highest activity in a certain assay, a conclusion about the exact type of M-o-A can be derived (Fig.…”
Section: Time-of-addition (T-o-a) Studiesmentioning
confidence: 99%